Economic Characteristics and Asset Allocation in the Context of De-Globalization - Wang, Zeyi (Transactions on Economics, Business and Management Research, 2024)
The world’s huge economy is often seen as a "whole", and within this huge "whole", there are countless components, the most obvious being is the state, influencing investment strategies and economic behaviors. This article aims to explore key economic characteristics and asset allocation strategies, focusing on family trusts in China amidst this de-globalization trend. The study highlights the necessity for asset allocation to adjust to the evolving economic landscape. To be specific, investors should minimize their dependence on global supply chains and pivot towards localized and regional assets. This includes a greater emphasis on domestic infrastructure projects and technology companies, which are likely to benefit from regional economic policies. Furthermore, it is prudent to increase investments in sectors that stand to gain from national or regional protectionist measures. Staying attuned to the changes in trade policies and government regulations will be crucial for optimizing returns and managing risks in a shifting global environment.